(untitled) (Historia, 2021)
1. Debates of the House of Assembly of the Union of South Africa as Reported in the Cape Times. First Session, fourth Parliament, 12th March, 1921 - 14th July, 1921 2. Hattersley, A. F. An Illustrated Social History of South Africa 3. Hauck, K.: Friihmittelalterliche Studies, Jahrbuch des Instituts fur Friih mittelatterforschung der Universitlt Munster 4. Lewis, I. M. History and Social Anthropology 5. Pearse, G. E.: Eighteenth Century Architecture in South Africa 6. Helman, A.: Zaken, zending en bezinning, De Romantische kroniek van een Tweehonderdjarige Surinaamse firma